Folic acid - importance for human health and its role in COVID-19 therapy - Katarzyna Kurowska; Milena Kobylińska; Katarzyna Antosik (National Institute of Public Health - National Institute of Hygiene, 2023)
Folic acid (folacin, B9) is a vitamin that performs many very important functions in the human body, and its inadequate level - deficiency as well as excess, may contribute to an increased risk of developing many disease processes. The aim of this study was to analyze the available scientific literature on folic acid and its impact on human health. A systematic review of the studies, published until November 2022, was made on the basis of searching bibliographic databases such as: PubMed, Elsevier and Google Scholar. The following keywords and combinations were used: folic acid, folate, folic acid supplementation, folate deficiency. Folic acid, thanks to its high biological activity, has a direct and indirect effect on the metabolism of the human body cells. It plays a very important role, among others in the prevention of neural tube defects and megaloblastic anemia, the proper functioning of the nervous system, as well as reducing the risk of developing certain cancers. Currently, the important role of folic acid in maintaining the proper functioning of the immune system is also emphasized, which is of particular importance both in the prevention and in the situation of SARS-CoV-2 (COVID-19) infection. The effects of deficiency and excess of vitamin B9 may turn out to be dangerous to health and even life. There is a need for nutritional and health education of the society regarding the importance of folic acid for human health, due to the presence of large deficiencies in the population, which is particularly important for some social groups, such as, for example, women of procreation age, pregnant or breastfeeding, people with a nutrient malabsorption, and people who smoke or abuse alcohol.